Practicality and Effectiveness of E-Worksheet Based on ExPRession Learning Model Activities to Train Critical Thinking Skills - Fenanda, Hindun Eka; Herlina, Kartini; Abdurrahman, Abdurrahman (Universitas Syiah Kuala, 2024)
Critical thinking skills are one of the essential abilities students must possess to face the developments in science and technology in 21st-century learning. The aim of this research is to describe the practicality and effectiveness of ExPRession-based e-worksheet activities in training critical thinking skills. The research design employed a pretest-posttest control group design. The research sample consisted of students from 12th-grade Science 1 and 3 at Public Senior High School Abung Semuli. Research instruments included observation sheets for lesson implementation, observation sheets for critical thinking activities, and critical thinking skills test sheets. Data on the practicality of learning were obtained through observations, while effectiveness data, in the form of critical thinking skills data, were obtained through pretest and posttest administration, and then analyzed using statistical formulas. Learning with ExPRession-based e-worksheets was deemed effective in training students' critical thinking abilities, as evidenced by the average N-Gain scores in the experimental group being higher than those in the control group. Based on these findings, critical thinking skills improved more significantly in the experimental group compared to the control group. Supported by the results of Independent Sample T-Test and Effect Size tests with a wide category, it can be concluded that ExPRession-based e-worksheet activities are effective in training students' critical thinking skills..